(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
The low student learning outcomes are motivated by the lack of activity of students during the learning process and the teacher’s dependence on textbooks. Therefore, this study aims to determine the effectiveness of 4C-based mathematics e-modules on the learning outcomes of grade VII students at UPTD SMP Negeri 1, Mungka District. This research was carried out with a quantitative research method in the form of a Quasy Experiment. The data collection technique used is a test in Mathematics subjects. The sample of this selection was 54 grade VII students consisting of 27 people from the experimental class and 27 people from the control class. The data analysis techniques are normality test, homogeneity test, and hypothesis test with the Wilcoxon Test test method. The results show that the use of 4C-based mathematics e-modules is significantly effective in improving the learning outcomes of grade VII students. If learning is facilitated with modules or e-modules based on the 4Cs, learning will be more effective, because after learning at school students can use the e-module, learning can be done independently by students.